Core tax administration system: the power and trust dimensions of slippery slope framework tax compliance model - I Nyoman Darmayasa; Nyoman Sentosa Hardika (Cogent Business & Management, 2024)
This research aims to understand whether the Core Tax Administration System (CTAS) will strengthen the power or the trust dimensions of the Slippery Slope Framework (SSF) tax compliance model. The research hypothesis is that the implementation of the CTAS will strengthen the power and the trust dimensions of the SSF tax compliance model. This qualitative study uses the Krippendorff content analysis technique. The data come from discourses by tax authorities and tax practitioners related to the CTAS published on YouTube channels. The study finds that the words that most often appear are `CTAS', `integrated', `data', `taxpayer compliance', `tax revenue', `comparative compliance arrangement', `identity number', `taxpayer registration number', `audit', `service', and `trust'. A number of the texts are related to strengthening the power to integrate taxpayer data to create comparative compliance arrangements and increase tax revenue. According to the SSF tax compliance model, which is formed on the concepts of power and trust, improving professional services using the CTAS will improve taxpayers' trust in the tax authority. This study answers the research hypothesis by finding that the implementation of the CTAS will begin by strengthening the power of the tax authority, and that this will be followed by increased trust. The Technology Acceptance Model (TAM) theory explains the increase in the tax authority's power through the implementation of the CTAS from the perspective of perceived usefulness. Strengthening this power gives legitimacy to the tax authority to develop programmes that support an increase in tax revenues after integrating the taxpayer profile data.
Keywords: 650; Core tax administration system; power or trust; slippery slope framework; tax compliance; technology acceptance mode